Locational Aspects of Industrial Ecology and Experiences of Practitioners from a Hungarian Industrial Park - Nagypál, Noémi Csigéné (European Journal of Sustainable Development, 2020)
The present article aims to contribute to understanding the relationship between the concepts of industrial ecology and circular economy in order to foster circular economy attempts. While research mostly focuses on various forms of industrial ecology or innovative technologies, it is also reasonable to analyse some mature industrial ecology practices, which can be used as quasi-models for circular economy. The technology selected for this study is flue gas desulphurisation in fossil fuel power plants and the utilization of gypsum produced in this process as a by-product by construction sector companies. In the first part of our article we briefly present the concept of industrial ecology and discuss its applicability as a potential model for circular economy as well as its locational aspects. Afterwards based on a literature review and stakeholder interviews a Hungarian power plant and industrial park is presented as a case study. The relevance of criteria of ecoinnovation parks are presented for the selected industrial park as well as the experience of industrial ecology by participating companies. Finally some general conclusions, based on the literature and the case study, are also discussed. Keywords: industrial ecology, locational aspects, industrial park, FGD gypsum